FAKTOR-FAKTOR YANG MEMPENGARUHI GANGGUAN PERNAFASAN PADA PEKERJA MEBEL DI MEDAN MAIMUN TAHUN 2023 - Susilawati Susilawati; Pinky Maeriska (CV. ADIBA AISHA AMIRA, 2024)
Wood processing Industry is afast growing industry and takes many humanresources. This type of industry hasadisadvantage that it can produce pollution formed as wood dust. Wood dust is a particulate coumpound which couldcause respiratory problem to workers if it entersthe respiratory tracts. Besidethe wood dust, there are some other factors from occupational to personal aspectsof workerswhich could cause respiratory symptoms.The aim study is analyze factors affecting respiratory symptoms. In Indonesia, the sick rate reaches 70% in workers who are exposed to dust every day. In 2013 the prevalence rate of Chronic Obstructive Pulmonary Disease(COPD) reached 3.7% and was more experienced by men. The amount of pulmonary function disorders can be influenced by dust and the characteristics of the workers themselves. This study aims to analyze the factors associated with impaired lung function in the furniture industry in Indonesia. The design of this study is a research with a literature review method. From the results of the search for scientific articles using the Google schoolar and GARUDA databases, 10 selected research articles were obtained. The results of the analysis showed that there was a relationship between wood dust levels and worker characteristics which included years of service, use of PPE, smoking habits, age, and length of exposure